The Influence of the Synthesis Temperature on Phase Composition and Structure of Tenary Compounds Obtained from the Powder Mixture of the TiH2-Al-C System - Bagliuk, G. A.; Suprun, O. V.; Mamonova, A. A. (Physics and Chemistry of Solid State, 2017)
This paper presents the results of an investigation of the features of phase and structure formation of a ternary compound during thermal sintering use of compacted TiH2-Al-C powder blends. The thermal sintering was carried out in a vacuum furnace at temperature 1150, 1300, and 1400 0С. The x-ray diffraction pattern and structural analysis show that the main phase after synthesis at 1150 0С is titanium carbide. The ternary Ti2AlC and intermetallic Ti3Al compound were also identified in the phase composition of the alloy. Increasing the sintering temperature to 1300 °C leads to significant increases in the content of Ti2AlC ternary compounds and accordingly decreases the content of titanium carbide TiC. Is propose a modified model thermal synthesis of ternary compounds of the Ti-Al-C system, which includes the melting of aluminum and its interaction with titanium at low-temperature stages of the process, the formation of the Ti3Al intermetallic compound, formation titanium carbide grains as a result of the interaction of the Al4C3 intermediate metastable phase with titanium or Ti3Al intermetallic compound and the synthesis of ternary Ti2AlC and Ti3AlC2 compounds as a result of the interaction of the Ti3Al intermetallic compound with carbon and Ti2AlC with titanium carbide TiC.